Perception of corporate social responsibility in a cooperative banks by their clients - Nowacka, Anna (Social Entrepreneurship Review, 2016)
The concept of corporate social responsibility is part of the strategy of cooperative banks since they were set up. The cooperative character of these institutions and their willingness to compete with other financial market players reflect the main assumptions of CSR. Cooperative banks, while pursuing their mission and vision, try to combine commercial goals with the social dimension of their business. The main purpose of the article is to present opinions of clients of cooperative banks on the implementation of corporate social responsibility by these institutions. The author attempts to answer the question, whether customers perceive the social aspect of cooperative banks operation and how they assess their approach to running a business. The empirical basis for the issues discussed in the article is a study of the literature on the subject and the survey results of 132 clients of selected cooperative banks. The questions concerned include: social initiatives undertaken by cooperative banks, forms of support provided by these institutions and participation of clients in events sponsored by cooperative banks. To develop the research results the following methods have been used: structural indicators and chi-squared compliance test. Following the results of the conducted research the general conclusion have been drawn. The most important of these is the fact, that the clients recognize social initiatives undertaken by cooperative banks. They appreciate the involvement of these institutions in promoting cultural and educational events as well as supporting and donating to social and charitable organizations. The idea of CSR is also realized through the process of financial education of the local community, and youth in particular.